21 Infective endocarditis post-transcatheter aortic valve implantation: experience from an irish tertiary referral centre. (30th September 2020) - Buckley, A; Armstrong, B; Tanner, R; Hassan, S; Moran, B; Byrne, J; Groarke, S; Margey, R; Casserly, I
Abstract : Background: Prior studies of infective endocarditis (IE) post-transcatheter aortic valve implantation (TAVI) have reported an incidence of 1–2%, a median time from TAVI to presentation with IE of ~1 year, and 1-year mortality rates of 40–50%. In addition, a higher rate of enterococci as the culprit microorganism compared to staphylococci and streptococci has been reported. Objectives: To determine the clinical characteristics, microorganism spectrum, and outcomes of IE post-TAVI in an Irish tertiary referral centre. Methods: Using a prospective TAVI database, all patients diagnosed with IE post-TAVI were identified. Pre-defined baseline demographic, procedural and follow-up data were analysed. Specific additional retrospective analysis of medical records were performed to assess the culprit microorganism and treatments for IE. Results: A total of 707 patients underwent TAVI during the study period. During a mean follow-up of 2.3 years, 17 (2.4%) patients with IE were identified. According to the modified Duke criteria, IE was defined as definite and probable in 6 (35%) and 11 (65%) cases, respectively. The mean age was 78.7 (±13.7) years and 12 (71%) were male. The median time from TAVI to presentation with IE was 7 months (IQR 5–13). The dominant culprit microorganisms identified were streptococci (41.1%), with a low frequency of enterococcus faecalis (17.6%) (table 1 ). Among the 17 patients with IE, there was one (6%) major stroke and two patients (12%) required surgical aortic valve replacement. There was one death during the initial hospitalization for IE. The Kaplan-Meier estimate of survival at 1 year was 0.82 (95% CI = 0.55–0.95) (figure 1 ). Conclusions: This Irish TAVI cohort exhibited a similar incidence of IE post-TAVI and similar time to first presentation compared to prior international registries. There was a much lower rate of enterococcus compared to staphylococci and streptococci as the culprit microorganism. The 1-year mortality rate in this series was much lower than previously reported.